2013
DOI: 10.1051/fruits/2013085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indigenous barberry germplasm in Pakistan: variability in morphological characteristics and nutritional composition

Abstract: -Introduction. Barberry (Berberis aristata DC.), a small fruit, is found growing in the wild in the temperate region of northern Pakistan. Materials and methods. Three different locations of Azad Jammu and Kashmir, i.e., Topa, Banjosa and Neriyan Sharif, were explored; thirty accessions of barberry were identified and characterized on the basis of their growth habit, flowering, fruiting and chemical composition of fruits. Results. The accessions exhibited high diversity in their phenotypical/morphological trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Climatic conditions, soil and locality influence the growth habit of tree. Tree shape, size, number and arrangement of leaves and branches depend upon light penetration into the tree canopy (Ahmed et al, 2013;2014). In the present study, the trees of most of the plum genotypes were upright and only three accessions had spreading growth habit.…”
Section: Resultsmentioning
confidence: 99%
“…Climatic conditions, soil and locality influence the growth habit of tree. Tree shape, size, number and arrangement of leaves and branches depend upon light penetration into the tree canopy (Ahmed et al, 2013;2014). In the present study, the trees of most of the plum genotypes were upright and only three accessions had spreading growth habit.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that genotypes with lower leaf dimensions had lengthier thorns. Ahmed et al (2013) reported the leaf length and leaf width in their investigated barberry ranged from 96.9 to 66.7 mm and 33.1 to 25.8 mm, respectively. The range of leaf length and leaf width in barberry genotypes studied by them was more than the values reported in the present study.…”
Section: Mean Comparisonmentioning
confidence: 92%
“…The length and width of the berries in the studied barberry were in the range 1.06-9 and 0.4-5.2 mm, respectively. In another study, the berry length varied from 9.75 to 7.12 mm, and the berry width was in the range 4.34-2.65 mm (Ahmed et al 2013). Goodarzi et al (2018) also investigated on the barberry genotypes in Khorasan-e-Jonoobi and reported that the berry length and berry width were in the range of 7.4-10.84 and 4.39-8.05 mm, respectively, which was more than the means of the berry length and berry width in this research.…”
Section: Mean Comparisonmentioning
confidence: 95%
See 2 more Smart Citations